Natural compound methyl protodioscin protects against intestinal inflammation through modulation of intestinal immune responses. Issue 2 (10th February 2015) - Zhang, Rongli; Gilbert, Shila; Yao, Xinsheng; Vallance, Jefferson; Steinbrecher, Kris; Moriggl, Richard; Zhang, Dongsheng; Eluri, Madhu; Chen, Haifeng; Cao, Huiqing; Shroyer, Noah; Denson, Lee; et al.
Abstract: Dioscoreaceae, a kind of yam plant, has been recommended for treatment of chronic inflammatory conditions. However, the mechanisms are poorly defined. Methyl protodioscin (MPD) is one of the main bioactive components in Dioscoreaceae . Here, we aim to determine the mechanisms by which MPD ameliorates intestinal inflammation. Surgical intestinal specimens were collected from inflammatory bowel diseases (IBD) patients to perform organ culture. Experimental colitis was induced in mice by dextran sulfate sodium (DSS) or Citrobacter rodentium, and was then treated with MPD. NF‐ κ B activation, expression of mucosal pro‐inflammatory cytokines, disease severity, and epithelial proliferation/apoptosis were determined. Mouse crypts and Caco‐2 monolayers were cultured to observe the effect of MPD upon intestinal epithelial differentiation and barrier function. We found that MPD increased the percentage of survival from high‐dose DSS‐(4%) treated mice, and accelerated mucosal healing and epithelial proliferation in low‐dose DSS‐(2.5%) treated mice characterized by marked reduction in NF‐ κ B activation, pro‐inflammatory cytokines expression and bacterial translocation. Consistently, MPD protected colonic mucosa from C. rodentium ‐induced colonic inflammation and bacterial colonization. In vitro studies showed that MPD significantly increased crypt formation and restored intestinal barrier dysfunction induced by pro‐inflammatory cytokines. In conclusion, MPD ameliorates the intestinal mucosal inflammation by modulating the intestinal immunity to enhance intestinal barrier differentiation. MPD could be an alternative for treating chronic intestinal inflammatory diseases. Abstract : e00118